2019
DOI: 10.1016/j.abrep.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Internet gaming disorder: Feeling the flow of social games

Abstract: Introduction Gaming Disorder (GD) was added to the recent publication of the International Classification of Diseases (ICD-11) by the World Health Organization. This aligns with recommendations of the fifth edition of the Diagnostic Statistical Manual for Mental Disorders (DSM-5), issued by the American Psychiatric Association. Accordingly, further relevant research has been invited. The interplay between preference for online social game genres, the degree of online Flow (or immersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 81 publications
4
66
1
3
Order By: Relevance
“…There is a wide range of game genres, these can include racing, shooting, puzzle, fighting, simulation, and role-playing games, available both in single player and/or multiplayer formats ( Anderson et al, 2017 ; Hu, Stavropoulos, Anderson, Scerri, & Collard, 2018 ; Scerri, Anderson, Stavropoulos, & Hu, 2018 ). Recent studies have shown that IGD susceptibility appears to vary across these game genres, with MMO games consistently corresponding with a higher risk due to its unique structural characteristics ( Kuss & Griffiths, 2012 ; Stavropoulos, Kuss, et al, 2017 ; Stavropoulos, Wilson, Kuss, Griffiths, & Gentile, 2017 ; Stetina et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide range of game genres, these can include racing, shooting, puzzle, fighting, simulation, and role-playing games, available both in single player and/or multiplayer formats ( Anderson et al, 2017 ; Hu, Stavropoulos, Anderson, Scerri, & Collard, 2018 ; Scerri, Anderson, Stavropoulos, & Hu, 2018 ). Recent studies have shown that IGD susceptibility appears to vary across these game genres, with MMO games consistently corresponding with a higher risk due to its unique structural characteristics ( Kuss & Griffiths, 2012 ; Stavropoulos, Kuss, et al, 2017 ; Stavropoulos, Wilson, Kuss, Griffiths, & Gentile, 2017 ; Stetina et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it is assumed that gamification processes could escalate into a form of addiction (Zhang et al, 2018b). The latter has attracted significant attention particularly after the introduction of Internet Gaming Disorder (IGD), as a disorder requiring further study (American Psychiatric Association [APA], 2013; Hu et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Despite OG having many positive psychosocial effects 1 beyond satisfying one's leisure needs Carras et al 2018;Jones et al 2014), for excessive gamers, psychosocial repercussions can be multiple, 2 compromising their concurrent and future adaptation (Anderson et al 2017;Beard et al 2017;Kuss and Griffiths 2012;Kuss et al 2017;Pontes et al 2017b;Kuss et al 2018;Stavropoulos et al 2018aStavropoulos et al , 2018bStavropoulos et al 2019). The extent and the significance of the excessive OG's negative repercussions have prompted questions and concerns regarding its classification as a distinct psychopathological entity and its inclusion in the broader category of addictive behaviors 3 (Kuss et al 2018;Hu et al 2018;Scerri et al 2018).…”
mentioning
confidence: 99%